Trauma and PTSD in older adults: Prevalence, course, concomitants and clinical considerations. (April 2017) - Cook, Joan M; Simiola, Vanessa
Highlights: Prevalence rates of PTSD are significantly lower for older adults. The development and course of PTSD in older adults may vary. Limited research has been conducted on interventions for older adults with PTSD. Abstract : This review presents recent empirical developments on Posttraumatic Stress Disorder (PTSD) in older adults, highlighting some of the most interesting lines of investigation that have taken place over the past few years. The majority of the extant literature has focused on male veterans or former prisoners of war, Caucasians, and those from the United States. Major advances have taken place in terms longitudinal investigations of representative samples of veterans and their health and functioning in relation to traumatic exposure. The current review explores the prevalence and impact, course and associated consequences, as well as available treatment for older adult survivors of traumatic experiences in an effort to increase education and awareness to improve overall health and functioning among this population.